Coagulation Profiles of Unexpected DCDD Donors Do Not Indicate a Role for Exogenous Fibrinolysis. Issue 3 (5th February 2015) - Vendrell, M.; Hessheimer, A. J.; Ruiz, A.; de Sousa, E.; Paredes, D.; Rodríguez, C.; Saavedra, S.; Fuster, J.; Alcaraz, A.; Oppenheimer, F.; Taurá, P.; García‐Valdecasas, J. C.; et al.
<x xml:space="preserve">Abstract</x> It has been suggested that vascular stasis during cardio‐circulatory arrest leads to the formation of microvascular thrombi and the viability of organs arising from donation after circulatory determination of death (DCDD) donors may be improved through the application of fibrinolytic therapy. Our aim was to comprehensively study the coagulation profiles of Maastricht category II DCDD donors in order to determine the presence of coagulation abnormalities that could benefit from fibrinolytic therapy. Whole blood from potential DCDD donors suffering out‐of‐hospital cardiac arrest was sampled after declaration of death in the emergency department, and rotational thromboelastomeric analysis was performed. Between July 2012 and December 2013, samples from 33 potential DCDD donors were analyzed. All patients demonstrated hyperfibrinolysis (HF), as reflected by maximum clot lysis of 98–100% in all cases, indicating that there is no role for additional fibrinolytic therapy in this setting. As well, we observed correlations between thromboelastomeric lysis parameters and maximum hepatic transaminase levels measured in potential donors and renal artery flows measured during ex situ hypothermic oxygenated machine perfusion, indicating that further studies on the utility of thromboelastometry to evaluate organ injury and perhaps even viability in unexpected DCDD may be warranted.